Preparation method of Ti3C2, Ti3C2, negative electrode material, battery piece and electric equipment
By etching Ti3C2 at low temperature using low eutectic molten salt, the problems of operation hazards, F functional group suppression and high energy consumption in the existing methods are solved, and efficient and low energy consumption Ti3C2 preparation is achieved, with excellent rate performance and high conductivity.
Patent Information
- Application Number
- CN202411598369.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-04-08
AI Technical Summary
The existing Ti3C2 preparation method has problems such as operating hazards, containing -F functional groups on the surface to inhibit ion storage and high energy consumption.
The low eutectic molten salt is used as the etching agent, and the salt is melted by heating in a closed container, and the etching reaction is carried out, and Ti3C2 is washed. The low-temperature operation of this method reduces energy consumption and avoids oxidation of Ti3C2.
It improves the preparation efficiency of Ti3C2, reduces the side effects of -F functional groups on charge storage, saves energy, and obtains excellent rate performance and high conductivity.
Smart Images

Figure CN119774613A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and in particular to a method for preparing Ti3C2, Ti3C2, anode materials, battery cells and electrical equipment. Background Art
[0002] Ti3C2 is a two-dimensional transition metal carbide, which is usually prepared from MAX (M represents transition metal, A represents main group element, X represents carbon or nitrogen) phase material by selectively etching away the A layer element (usually aluminum, gallium or silicon). As a new type of negative electrode material, Ti3C2 has metal-level conductivity, good two-dimensional morphology and rich surface functional groups, and exhibits excellent performance in batteries. In the related art, the preparation method of Ti3C2 is based on etching with a fluorine-based aqueous solution (including hydrofluoric acid, fluoride salts and HCl) as an etchant. However, the above preparation method is relatively dangerous to operate, and the surface of the obtained Ti3C2 contains -F functional groups, which are easy to inhibit the storage of ions. Another method is to use Lewis acids such as CuCl2+NaCl, FeCl2+NaCl, CuCl2+KCl, CuCl2+LiCl as etchants to prepare Ti3C2 negative electrode materials without fluorine on the surface. However, the etching temperature of the above-mentioned Lewis acid is above 500°C, which is easy to cause large energy consumption. Summary of the invention
[0003] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the first purpose of the present invention is to propose a method for preparing Ti3C2, improve the preparation efficiency of Ti3C2, reduce the side effect of the -F functional group on charge storage, and the low eutectic molten salt has a lower preparation temperature, saves energy consumption, and can also avoid oxidation of Ti3C2.
[0004] The second object of the present invention is to provide a Ti3C2.
[0005] The third object of the present invention is to provide a negative electrode material.
[0006] A fourth objective of the present invention is to provide a battery cell.
[0007] A fifth object of the present invention is to provide an electrical device.
[0008] The preparation method of Ti3C2 according to the first embodiment of the present invention comprises the following steps: Adding a low eutectic molten salt and a Ti3C2 matrix raw material into a closed container, wherein the low eutectic molten salt comprises: a first inorganic salt, a second inorganic salt, a third inorganic salt and a fourth inorganic salt, wherein the first inorganic salt is an aluminum salt, the second inorganic salt is a lithium salt, the third inorganic salt and the fourth inorganic salt are both selected from sodium salt and potassium salt, and the fourth inorganic salt is different from the third inorganic salt; heating to melt the eutectic molten salt to obtain a mixture, The mixture is washed to obtain Ti3C2.
[0009] According to the preparation method of Ti3C2 of the embodiment of the present invention, the low eutectic molten salt can be melted within the above temperature range to form a molten salt to etch the Ti3C2 matrix material. The melting temperature of the low eutectic molten salt is relatively low, which is beneficial to reduce the difficulty of preparing Ti3C2 and improve the preparation efficiency of Ti3C2. Ti3C2 prepared by low-temperature eutectic melting has a smaller interlayer spacing and high conductivity, and has excellent rate performance. Compared with the traditional aqueous solution preparation method, the side effect of the -F functional group on charge storage is reduced. Compared with the Lewis molten salt preparation method, the above low eutectic molten salt has a lower preparation temperature, saving energy consumption, and at the same time, the cation in the above low eutectic molten salt is Al 3+ , Li + 、Na + and / or K + , which is highly soluble and can be removed by washing (for example, washing with deionized water). Compared with the Lewis molten salt preparation method, it does not require post-treatment of strongly oxidizing ammonium persulfate to avoid oxidation of Ti3C2.
[0010] According to some embodiments of the present invention, the first inorganic salt is AlX, the second inorganic salt is LiX, the third inorganic salt and the fourth inorganic salt are both selected from NaX and KX, wherein X is selected from Cl, Br and I.
[0011] According to some embodiments of the present invention, the molar ratio of the first inorganic salt, the second inorganic salt, the third inorganic salt and the fourth inorganic salt is i:k:l:m, wherein the i, the k, the l and the m satisfy: 1≤i≤2, 0≤k≤1, 0≤l≤1, 0≤m≤1.
[0012] According to some embodiments of the present invention, the low eutectic molten salt further includes a fifth inorganic salt, and the fifth inorganic salt is MX, wherein the X is selected from Cl, Br and I, and the M is selected from Fe, Ag and Co.
[0013] According to some embodiments of the present invention, the molar ratio of the first inorganic salt, the second inorganic salt, the third inorganic salt, the fourth inorganic salt and the fifth inorganic salt is i:k:l:m:n, wherein the i, the k, the l, the m and the n satisfy: 1≤i≤2, 0≤k≤1, 0≤l≤1, 0≤m≤1, 0≤n≤1.
[0014] According to some embodiments of the present invention, the mass ratio of the Ti3C2 matrix material to the low eutectic molten salt is z, wherein z satisfies: 0.01≤z≤0.04.
[0015] According to some embodiments of the present invention, the Ti3C2 matrix raw material includes at least one of Ti3AlC2 and Ti3SiC2.
[0016] According to some embodiments of the present invention, the eutectic molten salt is pretreated before adding the eutectic molten salt and the Ti3C2 matrix raw material into the closed container. The pre-processing comprises the following steps: Drying the first inorganic salt in an inert atmosphere at a temperature range of 80° C. to 120° C. for 12 h to 36 h; and / or, The second inorganic salt, the third inorganic salt, the fourth inorganic salt and the fifth inorganic salt are dried at a temperature ranging from 80° C. to 120° C. for 12 h to 36 h.
[0017] According to some embodiments of the present invention, the Ti3C2 is dried by freeze drying at a temperature of -60°C to -40°C for a time of 24h to 48h.
[0018] According to some embodiments of the present invention, the Ti3C2 is dried by high-temperature vacuum drying, the pressure of the high-temperature vacuum drying is 10Pa-30Pa, the temperature is 60°C-100°C, and the time is 24h-48h.
[0019] According to some embodiments of the present invention, the heating method is oil bath heating, ultrasonic heating or oven heating.
[0020] According to some embodiments of the present invention, the sealed container is made of quartz, corundum, stainless steel or polytetrafluoroethylene.
[0021] According to the Ti3C2 of the embodiment of the second aspect of the present invention, the Ti3C2 is Ti3C2 prepared according to the preparation method of Ti3C2 of the embodiment of the first aspect of the present invention.
[0022] The negative electrode material according to the third aspect of the present invention comprises: Ti3C2, wherein the Ti3C2 is Ti3C2 prepared by the preparation method of Ti3C2 according to the first aspect of the present invention, or Ti3C2 according to the second aspect of the present invention.
[0023] The battery according to the fourth aspect of the present invention comprises: a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; wherein the negative electrode material of the negative electrode sheet is the negative electrode material according to the third aspect of the present invention.
[0024] An electrical device according to an embodiment of a fifth aspect of the present invention includes: a battery according to an embodiment of the fourth aspect of the present invention.
[0025] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which: Figure 1 is a schematic diagram of Ti3C2 according to Comparative Example 1 of the present invention; Figure 2 XRD spectra of Ti3C2 according to Example 1 of the present invention, Ti3C2 according to Comparative Example 1 and Ti3C2 parent material (002); Figure 3 is the electronic conductivity of Ti3C2 according to Example 1 of the present invention and Ti3C2 according to Comparative Example 1; Figure 4 is the electronic conductivity of Ti3C2 according to Example 1 of the present invention and Ti3C2 according to Comparative Example 2; Figure 5 The cyclic voltammetry curves (2 mVs -1 )contrast; Figure 6 is a capacity comparison between Ti3C2 according to Example 1 of the present invention and Ti3C2 according to Comparative Example 1; Figure 7 1 is the charge and discharge curve of Ti3C2 at different charging current densities according to Example 1 of the present invention; Figure 8 is a capacity comparison between Ti3C2 according to Example 2 of the present invention and Ti3C2 according to Comparative Example 1; Fig. 9 is a capacity comparison of Ti3C2 according to Example 3 of the present invention and Ti3C2 according to Comparative Example 1; Fig.10is a capacity comparison between Ti3C2 according to Example 4 of the present invention and Ti3C2 according to Example 1; Fig.11 It is the product yield of different parent content in Example 1 and Example 5 of the present invention. DETAILED DESCRIPTION
[0027] The following describes a method for preparing Ti3C2 according to an embodiment of the present invention.
[0028] The preparation method of Ti3C2 according to an embodiment of the present invention comprises the following steps: Add low eutectic molten salt and Ti3C2 matrix raw material into a closed container. The use of a closed container can avoid the influence of moisture in the environment on the low eutectic molten salt and the Ti3C2 matrix raw material, and at the same time, it can prevent the loss of vapor formed after the low eutectic molten salt melts to reduce the quality of the low eutectic molten salt, making the etching reaction more thorough, thereby improving the reliability of the etching of the Ti3C2 matrix raw material by the low eutectic molten salt, improving the quality of the prepared Ti3C2, and making Ti3C2 suitable for actual use needs.
[0029] Among them, the low eutectic molten salt includes: a first inorganic salt, a second inorganic salt, a third inorganic salt and a fourth inorganic salt, wherein the first inorganic salt is an aluminum salt, the second inorganic salt is a lithium salt, the third inorganic salt and the fourth inorganic salt are both selected from sodium salt and potassium salt, and the fourth inorganic salt is different from the third inorganic salt. There is a synergistic effect between the first inorganic salt, the second inorganic salt, the third inorganic salt and the fourth inorganic salt in the above-mentioned low eutectic molten salt, which is conducive to fully etching the Ti3C2 matrix material so that the obtained Ti3C2 meets the needs of actual production. Among them, the melting point of the low eutectic molten salt is low, and the free anions in the low eutectic molten salt can react with the groups between the Ti3C2 layers as nucleophiles without the need for desolvation. At the same time, the cations are inserted into the Ti3C2 interlayer, which is conducive to the peeling of the matrix material, so that the Ti3C2 prepared by low-temperature eutectic melting has a more suitable interlayer spacing and higher conductivity, so that Ti3C2 has a suitable ion transmission path and excellent rate performance. In this way, the large interlayer spacing of Ti3C2 can be avoided, which will weaken the interaction force between the layers, thereby avoiding the decrease in the mechanical strength of Ti3C2, and the large interlayer spacing can be avoided to affect the charge and discharge rate and cycle stability; at the same time, the small interlayer spacing can be avoided to limit the rapid migration of ions and reduce the energy density and power density of the battery.
[0030] Among them, there are four types of salts in the low eutectic molten salt, which is beneficial to lowering the melting point of the low eutectic molten salt. Aluminum salts can form coordinated anions with halogen elements to lower the melting point of the eutectic molten salt. The presence of lithium salts in the low eutectic molten salt is also beneficial to lowering the melting point of the eutectic molten salt. At the same time, the small particle size of Li +The addition of makes it easier to embed between layers during the etching process, resulting in a high etching yield. In addition, sodium and potassium salts can be used as supporting salts to provide a non-reactive ion background, help stabilize the chemical environment, and improve the selectivity and efficiency of etching. Therefore, the small ion size of lithium ions, aluminum ions, sodium ions, and potassium ions and the closed container make the etching yield higher, with the advantages of simple preparation process and low energy consumption.
[0031] Heat to melt the eutectic molten salt to obtain a mixture. The eutectic molten salt can melt within the above temperature range to form a molten salt to etch the Ti3C2 matrix material. The melting temperature of the eutectic molten salt in the above preparation method is relatively low, which is conducive to reducing the difficulty of preparing Ti3C2 and improving the preparation efficiency of Ti3C2. Compared with the traditional aqueous solution preparation method, the side effect of the -F functional group on charge storage is reduced. Compared with the Lewis molten salt preparation method, it has a lower preparation temperature and saves energy.
[0032] For example, in a glove box, low eutectic molten salt can be weighed in a certain proportion and placed in a high temperature resistant and sealed container, and then a certain amount of Ti3C2 matrix raw material is added, a stirring magnet is added, stirred evenly, and a sealing cover is covered to ensure sealing.
[0033] The mixture is washed to obtain Ti3C2. In addition, the cation in the above-mentioned low eutectic molten salt is Al 3+ , Li + 、Na + and / or K + , which is highly soluble and can be removed by washing (for example, washing with deionized water or washing with deionized water and ethanol alternately). Compared with the Lewis molten salt preparation method, it does not require post-treatment of strongly oxidizing ammonium persulfate to avoid oxidation of Ti3C2. At the same time, the mixture is impurity-removed to increase the purity of the obtained product Ti3C2, that is, the quality of Ti3C2 is improved, which is conducive to the application of Ti3C2 in actual production.
[0034] In addition, the above-mentioned preparation method of Ti3C2 does not need to be carried out under an inert atmosphere, which can further reduce the difficulty of preparing Ti3C2 and reduce the preparation cost of Ti3C2.
[0035] According to the preparation method of Ti3C2 of the embodiment of the present invention, the low eutectic molten salt can be melted within the above temperature range to form a molten salt to etch the Ti3C2 matrix material. The melting temperature of the low eutectic molten salt is relatively low, which is beneficial to reduce the difficulty of preparing Ti3C2 and improve the preparation efficiency of Ti3C2. Ti3C2 prepared by low-temperature eutectic melting has a smaller interlayer spacing and high conductivity, and has excellent rate performance. Compared with the traditional aqueous solution preparation method, the side effect of the -F functional group on charge storage is reduced. Compared with the Lewis molten salt preparation method, the above low eutectic molten salt has a lower preparation temperature, saving energy consumption, and at the same time, the cation in the above low eutectic molten salt is Al 3+ , Li + 、Na + and / or K + , which is highly soluble and can be removed by washing (for example, washing with deionized water). Compared with the Lewis molten salt preparation method, it does not require post-treatment of strongly oxidizing ammonium persulfate to avoid oxidation of Ti3C2.
[0036] According to some embodiments of the present invention, the first inorganic salt is AlX, the second inorganic salt is LiX, the third inorganic salt and the fourth inorganic salt are both selected from NaX and KX, wherein X is selected from Cl, Br and I. Among them, lithium halides with lower melting points (for example, the melting points of LiCl and LiBr are 605°C and 549°C, respectively) greatly reduce the preparation temperature (for example, the eutectic temperature of AlCl3-LiCl-NaCl-KCl can reach 75°C). For example, the melting point of LiCl (605°C) is lower than the melting point of NaCl (801°C) and the melting point of KC1 (770°C), which can greatly reduce the temperature of the eutectic molten salt (the temperature is 75°C, a reduction of about 20°C). In addition, Li + Size ComparisonNa + and K + The ions are small in size and are easier to embed between Ti3C2 layers during the etching process, thereby helping to improve the etching yield.
[0037] Further, the molar ratio of the first inorganic salt, the second inorganic salt, the third inorganic salt and the fourth inorganic salt is i:k:l:m, wherein i, k, l and m satisfy: 1≤i≤2, 0≤k≤1, 0≤l≤1, 0≤m≤1. The molar ratio of the first inorganic salt, the second inorganic salt, the third inorganic salt and the fourth inorganic salt is relatively reasonable, so as to give full play to the synergistic effect between the first inorganic salt, the second inorganic salt, the third inorganic salt and the fourth inorganic salt to complete the etching of the Ti3C2 matrix raw material.
[0038] According to some embodiments of the present invention, the low eutectic molten salt further includes a fifth inorganic salt, which is MX, wherein X is selected from Cl, Br and I, and M is selected from Fe, Ag and Co. The fifth inorganic salt is a transition metal salt. When Ti3C2 is applied to the negative electrode of the battery, the addition of the fifth inorganic salt provides the Ti3C2 product with redox active sites of transition metals and provides additional capacity, that is, when Ti3C2 is applied to the battery, more active sites are provided for the electrochemical reaction, thereby facilitating the improvement of the applicability of Ti3C2 and the improvement of the market competitiveness of Ti3C2.
[0039] Furthermore, the molar ratio of the first inorganic salt, the second inorganic salt, the third inorganic salt, the fourth inorganic salt and the fifth inorganic salt is i:k:l:m:n, wherein i, k, l, m and n satisfy: 1≤i≤2, 0≤k≤1, 0≤l≤1, 0≤m≤1, 0≤n≤1. The molar ratio of the first inorganic salt, the second inorganic salt, the third inorganic salt, the fourth inorganic salt and the fifth inorganic salt is relatively reasonable, giving full play to the role of the low eutectic molten salt, so that the fifth inorganic salt can play its full role to provide as many redox active sites of transition metals as possible for Ti3C2, while avoiding the cost increase caused by the excessive use of the fifth inorganic salt, and avoiding the presence of the fifth inorganic salt affecting the etching effect of the first inorganic salt, the second inorganic salt, the third inorganic salt and the fourth inorganic salt on the Ti3C2 matrix raw material.
[0040] According to some embodiments of the present invention, the mass ratio of the Ti3C2 matrix material and the low eutectic molten salt is z, wherein z satisfies: 0.01≤z≤0.04. The mass ratio of the Ti3C2 matrix material and the low eutectic molten salt is reasonable, which is conducive to achieving sufficient etching of the Ti3C2 matrix material by the low eutectic molten salt while avoiding excessive waste of the low eutectic molten salt or excessive etching of the Ti3C2 matrix material, thereby facilitating the control of the quality of the manufactured Ti3C2.
[0041] According to some specific embodiments of the present invention, the Ti3C2 matrix material includes at least one of Ti3AlC2 and Ti3SiC2. Ti3AlC2 is a typical MAX phase material. When preparing Ti3C2, the Al layer can be removed by chemical etching, leaving the Ti3C2 layer. Ti3SiC2 is also a MAX phase material, in which Si replaces the position of Al. When preparing Ti3C2MXene, the Si layer can be removed by chemical etching to obtain Ti3C2.
[0042] According to some embodiments of the present invention, the eutectic molten salt is pretreated before adding the eutectic molten salt and the Ti3C2 matrix raw material into a closed container.
[0043] The preprocessing includes the following steps: Drying the first inorganic salt in an inert atmosphere at a temperature range of 80° C. to 120° C. for 12 h to 36 h; and / or, The second inorganic salt, the third inorganic salt, the fourth inorganic salt and the fifth inorganic salt are dried at a temperature range of 80° C. to 120° C. for 12 h to 36 h.
[0044] The first inorganic salt is an aluminum salt, which can be prevented from reacting with moisture or other components in the air in an inert atmosphere (such as Ar). Therefore, all the above inorganic salts of the low eutectic molten salt are dried through pretreatment to remove water and avoid the influence of residual moisture on the etching process.
[0045] According to some embodiments of the present invention, Ti3C2 is dried by freeze drying, and the freeze drying temperature is -60°C to -40°C, and the time is 24h to 48h. Freeze drying directly converts the water in the material from solid to gas (sublimation) under low temperature and vacuum conditions, thereby avoiding chemical changes or physical damage that may be caused by the presence of liquid water. For Ti3C2, freeze drying can effectively retain its two-dimensional structure and properties. At the same time, freeze drying can also improve the stability of Ti3C2, making it more durable during storage and transportation. The above freeze drying temperature and time are relatively reasonable, and the moisture content in Ti3C2 is reduced to the required degree of dryness.
[0046] According to some other embodiments of the present invention, Ti3C2 is dried by high-temperature vacuum drying, and the pressure of high-temperature vacuum drying is 10Pa-30Pa, the temperature is 60℃-100℃, and the time is 24h-48h. High-temperature vacuum drying is a method of drying materials under high temperature and vacuum conditions. This method can effectively remove moisture or other volatile substances in Ti3C2 while reducing the occurrence of oxidation or other side reactions. For Ti3C2 (MXene) materials, high-temperature vacuum drying can help remove residual moisture or other solvents in the preparation process while maintaining the structural integrity and performance of Ti3C2. The above drying process is under reasonable low-pressure conditions, and the above temperature and time are relatively reasonable, which removes moisture from Ti3C2 while avoiding energy waste.
[0047] In addition, the heating method is oil bath heating, ultrasonic heating or oven heating. Oil bath heating usually uses silicone oil or other high-boiling point solvents such as castor oil as the medium, because the above liquid substances have high thermal stability and can be used in a wide temperature range). The advantages of oil bath heating are wide temperature range and uniform temperature. At the same time, the temperature control accuracy of heating is high, and heat can be transferred well, so that the low eutectic molten salt and Ti3C2 matrix raw materials in the closed container are heated evenly. Ultrasonic heating uses the cavitation effect generated by ultrasound in the liquid to produce local high temperature and high pressure areas, thereby indirectly causing the solution temperature to rise. Due to the cavitation effect, ultrasonic heating can rapidly increase the local temperature in a short time. When the oven is heated, the oven generates heat through electric heating elements, and circulates the hot air through fans and other devices to achieve the purpose of uniform heating. The operation of oven heating is simple and the temperature control is relatively accurate.
[0048] Therefore, the closed container is heated by oil bath heating, ultrasonic heating or oven heating, and the temperature control is more precise, which is conducive to the full melting of the low eutectic molten salt to achieve the etching of the Ti3C2 matrix raw material, thereby helping to improve the quality of the prepared Ti3C2.
[0049] According to some specific embodiments of the present invention, the material of the sealed container is quartz, corundum, stainless steel or polytetrafluoroethylene. Quartz vessels, corundum crucibles, stainless steel crucibles and polytetrafluoroethylene vessels all have good corrosion resistance and good sealing. At the same time, the above materials will not react with low eutectic molten salt and Ti3C2 matrix raw materials, and will not interfere with the preparation of the above Ti3C2, so the use of quartz, corundum, stainless steel or polytetrafluoroethylene sealed containers can meet the preparation needs of Ti3C2.
[0050] According to the Ti3C2 of the second embodiment of the present invention, Ti3C2 is Ti3C2 prepared according to the preparation method of Ti3C2 of the first embodiment of the present invention.
[0051] According to the Ti3C2 of the embodiment of the present invention, the quality of the Ti3C2 prepared by the above preparation method is good and suitable for meeting the actual use needs of Ti3C2.
[0052] The negative electrode material according to the third aspect of the present invention comprises: Ti3C2, wherein the Ti3C2 is Ti3C2 prepared by the preparation method of Ti3C2 according to the first aspect of the present invention, or the Ti3C2 according to the second aspect of the present invention.
[0053] The negative electrode material according to the embodiment of the present invention uses the above-mentioned Ti3C2, which is beneficial to improving the conductivity, chemical stability and mechanical strength of the negative electrode material, and is also beneficial to improving the theoretical capacity of the negative electrode material.
[0054] The battery according to the fourth embodiment of the present invention comprises: a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; wherein the negative electrode material of the negative electrode sheet is the negative electrode material according to the third embodiment of the present invention.
[0055] The battery according to the embodiment of the present invention, by adopting the above-mentioned negative electrode material, is conducive to improving the fast charging performance of the battery, thereby improving the user experience.
[0056] An electrical device according to an embodiment of a fifth aspect of the present invention includes: a battery according to an embodiment of the fourth aspect of the present invention.
[0057] The electric equipment according to the embodiment of the present invention adopts the above-mentioned battery, which improves the energy supply stability and reliability of the electric equipment, improves the use stability of the electric equipment, and improves the user experience of using the electric equipment, thereby helping to improve the market competitiveness of the electric equipment.
[0058] The embodiments of the present invention are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain the present invention, and cannot be interpreted as limiting the present invention. In addition, if not explicitly stated, all reagents used in the following embodiments are commercially available, or can be synthesized according to this article or known methods, and the reaction conditions not listed are also easily available to those skilled in the art.
[0059] Comparative Example 1 This comparative example provides a method for preparing a Ti3C2 negative electrode material and an electrode using a conventional fluorine-containing aqueous solution (LiF+HCl), which specifically includes the following steps: (1) Slowly add 1g of Ti3C2 matrix material (Ti3AlC2) into 30mL 6molL -1 The fluorine-containing acidic aqueous solution of HCl was stirred and mixed at a speed of 400 rpm and reacted at 35°C for 48 hours; (2) After the reaction is completed, wash the mixture 10 times by repeated centrifugation (at a speed of 2000 rpm) with deionized water until the pH is greater than 5; (3) Then, in an Ar atmosphere, ultrasonicate at 200 W for 60 min, centrifuge at 3500 rpm for 60 min, and pour off the supernatant; (4) Finally, the supernatant was freeze-dried at a freezing temperature of -50°C for 24 hours to obtain the Ti3C2 product prepared by the solution method in Comparative Example 1.
[0060] (5) The Ti3C2 obtained in step (4) was mixed with polyvinylidene fluoride (PVDF) and conductive carbon black (SuperP) in a ratio of 8:1:1 to prepare a slurry, which was then coated on a copper foil and punched into a small original electrode with a diameter of 12 mm. Finally, the small original electrode was assembled with a lithium sheet, a PP separator and an electrolyte (LiPF6, EC / EMC=3:7) into a button cell, and then the electrochemical performance was tested.
[0061] Comparative Example 2 This comparative example provides a method for preparing a Ti3C2 negative electrode material and an electrode using a low-temperature molten salt (without lithium halide), which specifically includes the following steps: (1) The raw materials required for the mixed molten salt are dried at high temperature and then sealed for future use: the inorganic salts NaCl and KCl need to be dehydrated and dried at 100°C for 24 hours before use, but AlCl3 needs to be dehydrated and dried at 80°C for 24 hours in an Ar atmosphere.
[0062] (2) In a glove box, weigh the mixed salt material according to a certain proportion and place it in a high-temperature resistant corundum crucible, then add a certain amount of Ti3AlC2 matrix raw material, add a stirring magnet, and stir evenly. The molten salt system used in this comparative example is composed of three inorganic salts: AlCl3, NaCl and KCl, and is prepared according to the molar ratio of AlCl3+0.1NaCl+0.2KCl. After preparation, take 30g of the solid salt mixture and put it into a corundum crucible, then add 0.6g of Ti3AlC2 powder according to the mass ratio of matrix to molten salt z=0.02, and then cover the lid to ensure sealing.
[0063] (3) Place the corundum crucible in a protective gas atmosphere and heat it at high temperature to dissolve the salt into liquid, and continue heating for a period of time to perform the etching reaction. Place the corundum crucible containing solid salt and Ti3AlC2 in an Ar gas protective atmosphere, heat it at a rate of 5°C / min, and then continue heating at 140°C for 12 hours.
[0064] (4) After the reaction is completed, the prepared Ti3C2 negative electrode material is obtained by repeated washing. Specifically, the product is cooled to room temperature, the molten salt is washed away with deionized water, and the product is obtained at a speed of 2000prm in a centrifuge after 8 washings with deionized water, and then dried at a freezing temperature of minus 50°C for 24 hours to obtain the Ti3C2 product prepared by comparative example 2 using a low eutectic molten salt without lithium halide.
[0065] Example 1 This embodiment provides a method for preparing a Ti3C2 negative electrode material and an electrode from a low-temperature molten salt, which specifically includes the following steps: (1) The raw materials required for the low eutectic molten salt are dried at high temperature and then sealed and stored for future use: the inorganic salts NaCl, KCl and LiCl need to be dehydrated and dried at 100°C for 24 hours before use, but AlCl3 needs to be dehydrated and dried at 80°C for 24 hours in an Ar atmosphere.
[0066] (2) In a glove box, weigh the mixed salt material according to a certain proportion and place it in a high-temperature resistant and sealed container, then add a certain amount of Ti3AlC2 matrix raw material, add a stirring magnet, stir evenly, and cover the sealing cover. The molten salt system used in this patent is composed of four common inorganic salts: AlCl3, NaCl, KCl and LiCl, and is prepared according to the molar ratio of AlCl3+0.1NaCl+0.2KCl+1.5LiCl. After preparation, take 30g of the solid salt mixture in a quartz container with a lid, then add 0.6g of Ti3AlC2 black powder according to the mass ratio of Ti3C2 matrix raw material to low eutectic molten salt z=0.02, and then cover the lid to ensure sealing.
[0067] (3) Heat the sealed container at high temperature to dissolve the salt into a solution, and continue heating under stirring to perform the etching reaction. Place the quartz container containing solid salt and Ti3AlC2 in silicone oil and dissolve them into liquid molten salt at 140°C, with a heating rate of 5°C / min, and then stir at a speed of 500rpm for 12 hours.
[0068] (4) After the reaction is completed, the prepared Ti3C2 negative electrode material is obtained by repeated washing. Specifically, the product is cooled to room temperature, the molten salt is washed away with deionized water, and the product is obtained at a speed of 2000prm in a centrifuge after 8 washings with deionized water, and then dried at a freezing temperature of minus 50°C for 24 hours to obtain the Ti3C2 prepared in this patent.
[0069] (5) The Ti3C2 obtained in step (4) was mixed with PVDF and SuperP in a ratio of 8:1:1 to prepare a slurry, which was then coated on a copper foil and punched into a small original electrode with a diameter of 12 mm. Finally, the small original electrode was assembled with a lithium sheet, a PP separator and an electrolyte (LiPF6, ethylene carbonate (EC) / ethyl methyl carbonate (EMC) = 3:7) into a button cell, and then the performance test was carried out.
[0070] Example 2 This embodiment provides a method for preparing a Ti3C2 negative electrode material and an electrode from a low-temperature molten salt, which specifically includes the following steps: (1) The raw materials required for the low eutectic molten salt are dried at high temperature and then sealed and stored for future use: the inorganic salts NaBr, KBr and LiBr need to be dehydrated and dried at 100°C for 24 hours before use, but AlCl3 needs to be dehydrated and dried at 80°C for 24 hours in an Ar atmosphere.
[0071] (2) In a glove box, weigh the mixed salt material according to a certain proportion and place it in a high-temperature resistant and sealed container, then add a certain amount of Ti3AlC2 matrix raw material, add a stirring magnet, stir evenly, and cover the sealing cover. The molten salt system used in this patent is composed of four common inorganic salts: AlCl3, NaBr, KBr and LiBr, and is prepared according to the molar ratio of AlCl3+0.1NaBr+0.2KBr+1.5LiBr. After preparation, take 30g of the solid salt mixture and put it into a quartz container with a lid, then add 0.6g of Ti3AlC2 black powder according to the mass ratio of Ti3C2 matrix raw material to low eutectic molten salt z=0.02, and then cover the lid to ensure sealing.
[0072] (3) Heat the sealed container at high temperature to dissolve the salt into liquid, and continue heating under stirring to perform etching reaction. Place the quartz container containing solid salt and Ti3AlC2 in silicone oil and dissolve them into liquid molten salt at 170℃, with a heating rate of 5℃ / min, and then stir at 500rpm for 12h.
[0073] (4) After the reaction is completed, the prepared Ti3C2 negative electrode material is obtained by repeated washing. Specifically, the product is cooled to room temperature, the molten salt is washed away with deionized water, and the product is obtained at a speed of 2000prm in a centrifuge after 8 washings with deionized water, and then dried at a freezing temperature of minus 50°C for 24 hours to obtain the Ti3C2 prepared in this patent.
[0074] (5) The Ti3C2 obtained in step (4) was mixed with PVDF and SuperP in a ratio of 8:1:1 to prepare a slurry, which was then coated on a copper foil and punched into a small original electrode with a diameter of 12 mm. Finally, the small original electrode was assembled with a lithium sheet, a PP separator and an electrolyte (LiPF6, EC / EMC=3:7) into a button cell, and then the performance test was carried out.
[0075] Example 3 This embodiment provides a method for preparing a Ti3C2 negative electrode material and an electrode from a low-temperature molten salt, which specifically includes the following steps: (1) The raw materials required for the low eutectic molten salt are dried at high temperature and then sealed and stored for future use: the inorganic salts NaCl, KCl and LiCl need to be dehydrated and dried at 100°C for 24 hours before use, but AlBr3 needs to be dehydrated and dried at 80°C for 24 hours in an Ar atmosphere.
[0076] (2) In a glove box, weigh the mixed salt material according to a certain proportion and place it in a high-temperature resistant and sealed container, then add a certain amount of Ti3SiC2 matrix raw material, add a stirring magnet, stir evenly, and cover the sealing cover. The molten salt system used in this patent is composed of four common inorganic salts: AlBr3, NaCl, KCl and LiCl, and is prepared according to the molar ratio of AlBr3+0.1NaCl+0.2KCl+1.5LiCl. After preparation, take 30g of the solid salt mixture and put it into a quartz container with a lid, then add 0.6g of Ti3SiC2 powder according to the mass ratio of Ti3C2 matrix raw material to low eutectic molten salt z=0.02, and then cover the lid to ensure sealing.
[0077] (3) Heat the sealed container at high temperature to dissolve the salt into liquid, and continue heating for a period of time under stirring to carry out the etching reaction. Place the quartz container containing solid salt and Ti3AlC2 in silicone oil at 140°C to dissolve into liquid molten salt, with a heating rate of 5°C / min, and then stir at 500rpm for 12h.
[0078] (4) After the reaction is completed, the Ti3C2 negative electrode material is obtained by repeated washing. Specifically, the material is cooled to room temperature, the molten salt is washed away with deionized water, and the product is obtained at a centrifuge speed of 2000 prm after 8 washings with deionized water. The product is then dried at a freezing temperature of -50°C for 24 hours to obtain the Ti3C2 prepared in this patent.
[0079] (5) The Ti3C2 obtained in step (4) was mixed with PVDF and SuperP in a ratio of 8:1:1 to prepare a slurry, which was then coated on a copper foil and punched into a small original electrode with a diameter of 12 mm. Finally, the small original electrode was assembled with a lithium sheet, a PP separator and an electrolyte (LiPF6, EC / EMC=3:7) into a button cell, and then the performance test was carried out.
[0080] Example 4 This embodiment provides a method for preparing a Ti3C2 negative electrode material and an electrode from a low-temperature molten salt, which specifically includes the following steps: (1) The raw materials required for the low eutectic molten salt are dried at high temperature and then sealed for future use: the inorganic salts NaCl, KCl, LiCl and FeCl2 need to be dehydrated and dried at 100°C for 24 hours before use, but AlCl3 needs to be dehydrated and dried at 80°C for 24 hours in an Ar atmosphere.
[0081] (2) In a glove box, weigh the mixed salt material according to a certain proportion and place it in a high-temperature resistant and sealed container, then add a certain amount of Ti3AlC2 matrix raw material, add a stirring magnet, stir evenly, and cover the sealing cover. The molten salt system used in this patent is composed of five common inorganic salts: AlBr3, NaCl, KCl, LiCl and FeCl2, and is prepared according to the molar ratio of AlBr3+0.1NaCl+0.2KCl+1.5LiCl+0.01FeCl2. After preparation, take 30g of the solid salt mixture and put it into a quartz container with a lid, then add 0.6g of Ti3AlC2 powder according to the mass ratio of Ti3C2 matrix raw material to low eutectic molten salt z=0.02, and then cover the lid to ensure sealing.
[0082] (3) Heat the sealed container at high temperature to dissolve the salt into liquid, and continue heating under stirring to perform etching reaction. Place the quartz container containing solid salt and Ti3AlC2 in silicone oil and dissolve it into liquid molten salt at 140℃, with a heating rate of 5℃ / min, and then stir at 500rpm for 12h.
[0083] (4) After the reaction is completed, the Ti3C2 negative electrode material is obtained by repeated washing. Specifically, the material is cooled to room temperature, the molten salt is washed away with deionized water, and the product is obtained at a centrifuge speed of 2000 prm after 8 washings with deionized water. The product is then dried at a freezing temperature of -50°C for 24 hours to obtain the Ti3C2 prepared in this patent.
[0084] (5) The Ti3C2 obtained in step (4) was mixed with PVDF and SuperP in a ratio of 8:1:1 to prepare a slurry, which was then coated on a copper foil and punched into a small original electrode with a diameter of 12 mm. Finally, the small original electrode was assembled with a lithium sheet, a PP separator and an electrolyte (LiPF6, EC / EMC=3:7) into a button cell, and then the performance was tested.
[0085] Example 5 This embodiment provides a method for preparing a Ti3C2 negative electrode material and an electrode using a low-temperature molten salt (containing an excessive amount of Ti3C2 matrix raw material), which specifically includes the following steps: (1) The raw materials required for the low eutectic molten salt are dried at high temperature and then sealed and stored for future use: the inorganic salts NaCl, KCl and LiCl need to be dehydrated and dried at 100°C for 24 hours before use, but AlCl3 needs to be dehydrated and dried at 80°C for 24 hours in an Ar atmosphere.
[0086] (2) In a glove box, weigh the mixed salt material according to a certain proportion and place it in a high-temperature resistant and sealed container, then add a certain amount of Ti3AlC2 matrix raw material, add a stirring magnet, stir evenly, and cover the sealing cover. The molten salt system used in this patent is composed of four common inorganic salts: AlCl3, NaCl, KCl and LiCl, and is prepared according to the molar ratio of AlCl3+0.1NaCl+0.2KCl+1.5LiCl. After preparation, take 30g of the solid salt mixture in a quartz container with a lid, and then add 1.2g, 1.35g, 1.5g and 2.4g of Ti3AlC2 black powder according to the mass ratio of Ti3C2 matrix raw material to low eutectic molten salt z=0.04, 0.045, 0.05 and 0.08 respectively, and then cover the lid to ensure sealing.
[0087] (3) Heat the sealed container at high temperature to dissolve the salt into a solution, and continue heating under stirring to perform the etching reaction. Place the quartz container containing solid salt and Ti3AlC2 in silicone oil and dissolve them into liquid molten salt at 140°C, with a heating rate of 5°C / min, and then stir at a speed of 500rpm for 12 hours.
[0088] (4) After the reaction is completed, the prepared Ti3C2 negative electrode material is obtained by repeated washing. Specifically, the material is cooled to room temperature, the molten salt is washed away with deionized water, and the product is obtained by washing with deionized water 8 times at a speed of 2000 prm in a centrifuge, and then dried at a freezing temperature of minus 50°C for 24 hours to obtain the product obtained in Comparative Example 3.
[0089] Performance Testing The method and parameters of the electrochemical test are as follows: Use an electrochemical workstation or other charging and discharging equipment to perform constant current charge and discharge tests and cyclic voltammetry tests on the battery. The current densities of constant current charge and discharge are 1A g -1 , 2A g -1 , 5A g -1 , 10Ag -1 The potential range is 0.05V~3V; the scanning rate of cyclic voltammetry test is 1mVs -1 , 2mVs -1 , 5mVs -1 , 20mVs -1 , 50mVs -1 , 100mVs-1 , the potential range is 0V~3V.
[0090] Test results analysis The product prepared in Example 1 exhibits an accordion-like layered material ( Figure 1 ), indicating that the Ti3C2 matrix material peeled off and its (002) position decreased from 9.8° to 9.4° ( Figure 2 ), further indicating that the Ti3C2 matrix material was etched and peeled off in the current low-temperature molten salt system, causing its diffraction angle to shift to a smaller angle and the interlayer spacing to increase. Therefore, it can be known that Ti3C2 was successfully prepared under the conditions of Example 1. The peak position of the conventional aqueous solution (002) in Comparative Example 1 is 7.0°, which means that the interlayer spacing of Ti3C2 prepared in the comparative example is much larger than that of Ti3C2 prepared in Example 1. By testing the electronic conductivity of the two products, the results show that the electronic conductivity of the product in Example 1 (11264.9S m -1 ) is higher than that in Example 1 (7042.4S m -1 ) should be high ( Figure 3 ), which is mainly related to the reasonable interlayer spacing of the product prepared by the present invention, so that the product Ti3C2 of the present invention has the potential for high rate performance. From the experimental data, the product yield of comparative example 2 is ~28% without adding lithium chloride, while the product yield of example 1 is as high as 60% ( Figure 4 ), indicating that etching of lithium chloride in a closed container can not only reduce the eutectic temperature of the molten salt, but also greatly promote the etching reaction efficiency. From the product yield data of Example 1 and Example 5 ( Fig.11 ), when z is greater than 0.04, the yield drops sharply, indicating that too much Ti3C2 matrix should not be added.
[0091] The material prepared in Example 1 was assembled into a button cell and then the electrochemical performance was tested. -1 At a scan rate of , the area of the cyclic voltammetry curve (CV) of Ti3C2 prepared by the molten salt method is larger than the CV area of Ti3C2 prepared by the conventional solution method in Comparative Example 1 ( Figure 5 ), indicating that Ti3C2 prepared by the molten salt method has a higher charge storage capacity, which is mainly related to the surface groups with higher activity in the fluorine-free environment of low-temperature molten salt. In order to evaluate the capacity retention performance of electrode materials at different scan rates, Ti3C2 prepared by the molten salt method was tested at 1mVs -1 At a scan rate of 179.4 mAh g -1 The specific capacity of the solution method in Comparative Example 1 is 149.3 mAh g -1 . At 100mVs -1At a scan rate of 1.3 %, the specific capacity of Ti3C2 prepared by the molten salt method remained at 85.8 mAh g -1 The capacity retention rate is 47.8%, while the specific capacity of Ti3C2 prepared by solution method is 21.6 mAh g -1 , the capacity retention rate is 14.5% ( Figure 6 ), indicating that Ti3C2 prepared by molten salt method has better rate performance, which may be related to the fact that there is basically no oxygen in low-temperature molten salt, which prevents the material from being oxidized and damaged, and has higher electronic conductivity. -1 At a current density of 189.7 mAh g -1 The specific capacity of 1A g -1 The current density is 108.6 mAh g -1 The specific capacity and capacity retention rate are 57.2% ( Figure 7 ), which again shows that Ti3C2 prepared by molten salt method can -1 ) has good rate performance under high temperature.
[0092] Example 2 is the Ti3C2 prepared by etching with the bromide inorganic salt system of NaBr, KBr and LiBr. To verify the feasibility of etching with different halide molten salt systems, the prepared products were assembled into a button and the electrochemical performance was tested. The specific results are as follows: at 1mVs -1 At a scan rate of 165.2 mAhg -1 The specific capacity of the solution method is 149.3 mAhg -1 ; and at 100mVs -1 At a scan rate of 1.3 %, the specific capacity of Ti3C2 prepared by the molten salt method remained at 64.0 mAh g -1 The capacity retention rate is 38.7%, while the specific capacity of Ti3C2 prepared by solution method is 21.6 mAh g -1 , the capacity retention rate is 14.5% ( Figure 8 ), indicating that Ti3C2 prepared by bromide molten salt method has better rate performance.
[0093] In this embodiment 3, Ti3C2 was prepared by etching Ti3SiC2 in a low-temperature molten salt system to verify that different Ti3C2 matrix materials can also be used to prepare high-performance electrode materials in a low-temperature molten salt system. The electrode materials were assembled into a button test to test their electrochemical properties. The specific results are as follows: -1 At a scan rate of 171.7 mAhg -1 The specific capacity of the solution method is 149.3 mAhg -1 ; and at 100mVs -1At a scan rate of 1.3 %, the specific capacity of Ti3C2 prepared by the molten salt method remained at 66.7 mAh g -1 The capacity retention rate is 38.8%, while the specific capacity of Ti3C2 prepared by solution method is 21.6 mAh g -1 , the capacity retention rate is 14.5% ( Fig. 9 ), indicating that Ti3C2 prepared by molten salt method has better rate performance.
[0094] Example 4 is a Ti3C2 prepared using a molten salt system of FeCl2, NaCl, KCl, LiCl and AlCl3. To verify the effect of the addition of transition metal halide salts on the performance, the prepared products were assembled into a button battery and the electrochemical performance was tested. The specific test results of this Example 4 are as follows: at 1mVs -1 At a scan rate of 187.2 mAh g -1 The specific capacity at 100mVs -1 At a scan rate of 1 mVs -1 At a scan rate of 179.4 mAhg -1 The specific capacity at 1mVs -1 The capacity retention rate is 47.8% ( Fig.10 ). These results indicate that the addition of FeCl2 increases the capacity at low rates, but reduces the capacity at high rates, which is mainly related to the redox active sites provided by the transition metal.
[0095] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the exemplary expressions of the above terms do not necessarily refer to the same embodiment or example.
[0096] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.
Claims
1. A method for preparing Ti3C2, characterized in that: The following steps are involved: Adding a low eutectic molten salt and a Ti3C2 matrix raw material into a closed container, wherein the low eutectic molten salt comprises: a first inorganic salt, a second inorganic salt, a third inorganic salt and a fourth inorganic salt, wherein the first inorganic salt is an aluminum salt, the second inorganic salt is a lithium salt, the third inorganic salt and the fourth inorganic salt are both selected from sodium salt and potassium salt, and the fourth inorganic salt is different from the third inorganic salt; heating to melt the eutectic molten salt to obtain a mixture; The mixture is washed to obtain Ti3C2.
2. The method for preparing Ti3C2 according to claim 1, characterized in that: The first inorganic salt is AlX, the second inorganic salt is LiX, the third inorganic salt and the fourth inorganic salt are both selected from NaX and KX, wherein X is selected from Cl, Br and I.
3. The method for preparing Ti3C2 according to claim 2, characterized in that: The molar ratio of the first inorganic salt, the second inorganic salt, the third inorganic salt and the fourth inorganic salt is i:k:l:m, Wherein, the i, the k, the l and the m satisfy: 1≤i≤2, 0≤k≤1, 0≤l≤1, 0≤m≤1.
4. The method for preparing Ti3C2 according to claim 2, characterized in that: The low eutectic molten salt further includes a fifth inorganic salt, and the fifth inorganic salt is MX, wherein the X is selected from Cl, Br and I, and the M is selected from Fe, Ag and Co.
5. The method for preparing Ti3C2 according to claim 4, characterized in that: The molar ratio of the first inorganic salt, the second inorganic salt, the third inorganic salt, the fourth inorganic salt and the fifth inorganic salt is i:k:l:m:n, Among them, the i, the k, the l, the m and the n satisfy: 1≤i≤2, 0≤k≤1, 0≤l≤1, 0≤m≤1, 0≤n≤1.
6. The method for preparing Ti3C2 according to claim 1, characterized in that: The mass ratio of the Ti3C2 matrix material to the low eutectic molten salt is z, wherein z satisfies: 0.01≤z≤0.
04.
7. The method for preparing Ti3C2 according to claim 6, characterized in that: The Ti3C2 matrix material includes at least one of Ti3AlC2 and Ti3SiC2.
8. The method for preparing Ti3C2 according to any one of claims 1 to 7, characterized in that: The low eutectic molten salt is pretreated before adding the low eutectic molten salt and the Ti3C2 matrix raw material into the closed container, The pre-processing comprises the following steps: Drying the first inorganic salt in an inert atmosphere at a temperature range of 80° C. to 120° C. for 12 h to 36 h; and / or, The second inorganic salt, the third inorganic salt, the fourth inorganic salt and the fifth inorganic salt are dried at a temperature ranging from 80° C. to 120° C. for 12 h to 36 h.
9. The method for preparing Ti3C2 according to any one of claims 1 to 7, characterized in that: The Ti3C2 is dried by freeze drying at a temperature of -60°C to -40°C for 24h to 48h.
10. The method for preparing Ti3C2 according to any one of claims 1 to 7, characterized in that: The Ti3C2 is dried by high-temperature vacuum drying. The pressure of the high-temperature vacuum drying is 10Pa-30Pa, the temperature is 60°C-100°C, and the time is 24h-48h.
11. The method for preparing Ti3C2 according to any one of claims 1 to 7, characterized in that: The heating method is oil bath heating, ultrasonic heating or oven heating.
12. The method for preparing Ti3C2 according to any one of claims 1 to 7, characterized in that: The sealed container is made of quartz, corundum, stainless steel or polytetrafluoroethylene.
13. A Ti3C2, characterized in that The Ti3C2 is Ti3C2 prepared according to the preparation method of Ti3C2 described in any one of claims 1-12.
14. A negative electrode material, characterized in that: include: Ti3C2, wherein the Ti3C2 is Ti3C2 obtained by the preparation method of Ti3C2 according to any one of claims 1 to 12, or the Ti3C2 according to claim 13.
15. A battery, characterized in that: include: A positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; wherein the negative electrode material of the negative electrode sheet is the negative electrode material according to claim 14.
16. An electrical equipment, characterized in that: include: A battery according to claim 15.